COP ENHANCEMENT OF VAPOUR COMPRESSION REFRIGERATION SYSTEM USING DEDICATED MECHANICAL SUBCOOLING CYCLE. (Nigerian Journal of Technology, 2020)
This study focused on development of an improved vapour compression refrigeration system (IVCR system). Dedicated mechanical subcooling cycle is employed in attaining the developed IVCR system. The system is composed of two cycles cascade refrigeration system working with R134a. It consists of a rectangular shape with total storage space of 0.582 m3, made of galvanized mild steel and internally insulated with 0.05 m polystyrene foam. Tests under a wide range operating temperature conditions were carried out on the developed IVCR system. Performance evaluation of the system was characterized in terms of cooling capacity and coefficient of performance (COP). Experimental results showed that the COP of the subcooled system improved better than that of the main system from 18.0% to about 33.5% over an evaporating temperature range of -10 to 30oC. It can be concluded that the use of dedicated sub cooling cycle in VCR system is more efficient and suitable for the betterment of thermal system performance. http://dx.doi.org/10.4314/njt.v39i3.17